Errors in Purchasing Land Rights Which Result in Criminal Liability (Case Study of the Application of Article 385 Paragraph 1 of the KUHP in Cases of Land Grabbing) - Murdipin Hadi; Yusuf M. Said (Fox Justi : Jurnal Ilmu Hukum, 2025)
Basically, the difference in court decisions in land grabbing cases is a problem related to the fulfillment of the elements of the crime in Article 385 paragraph (1) of the Criminal Code that can be criminally accounted for. The fulfillment of the elements of the crime in question certainly has a correlation with the determination of the defendant which is the consideration of the Panel of Judges in the case. Therefore, in this study there are problems, namely: 1. Can the act of purchasing land rights be categorized as an error that can be criminally accounted for? 2. How is the legal consideration of the Panel of Judges in applying Article 385 Paragraph 1 of the Criminal Code that can cause differences in criminal decisions in land grabbing cases viewed from the theory of legal certainty? The research method used is a normative juridical research that will examine court decisions regarding land grabbing cases that have permanent legal force. The court decision will be examined based on the legal provisions contained in the Old Criminal Code. The results of the study conclude that: 1. Actions that can be categorized as criminal acts, namely: a. Actions intended to benefit oneself or others unlawfully; b. Selling, exchanging, or encumbering with a right to land, a building, structure, planting, or seeding. Meanwhile, the aspect of error in criminal acts in the crime of land grabbing as regulated in Article 385 Paragraph 1 of the Criminal Code relates to "even though it is known that the one who has or also has rights to it is another person". 2. There are different views from the Panel of Judges in the decision of the crime of land grabbing as regulated in Article 385 Paragraph 1 of the Criminal Code in the Decision of the Palangkaraya District Court Number: 53 / Pid.B / 2018 / PN.Plk dated May 7, 2018, which emphasizes more on the legal position of the Defendant as a land buyer, while in the Decision of the Supreme Court Number: 683 K / PID / 2018.